Analysis Of The Impact Of The Implementation Of The Regent's Authority Policy To The Camat - Try Adhi Bangsawan (Lembaga Pengembangan Kinerja Dosen, 2024)
Entering the era of regional autonomy, delegating the regent's authority to the Camat as an administrative extension at the sub-district level is very important. The delegation of authority can assist the duties and responsibilities in implementing government. In addition, the delegation of authority is also a benchmark for improving employee performance, especially at the sub-district level. The objectives of this study are: 1) how much influence does the implementation of the policy of delegation of authority of the Regent of Lebak to the Sub-District Head have on employee performance? 2) How much influence does policy implementation have through basic measures and policy objectives and sources, inter-organizational communication, implementation activities, implementing agency characteristics, economic, social, and political conditions, and implementing tendencies? 3) inhibiting indicators in implementing the policy of delegating part of the regent's authority to the Sub-District Head and the efforts made in overcoming these obstacles. The findings of this study are based on the reliability results, which show that the standardized item alpha of the Policy Implementation variable and the Employee Performance variable are in the reliability index standard. The data is declared reliable and can be considered representative, or at least close to the measured variable. Then, the results of the Regression equation show that there is a significant influence of 27.2%, meaning that the Policy Implementation variable on the performance of Bayah District employees, Lebak Regency, Banten Province have a strong enough so that other factors that are not measured have a reasonably weak influence. Then, based on the Coefficient of determination, it shows that the implementation of the policy of delegation of some authority affects the performance of employees in Bayah District and has a strong influence.